Comparison of Outcomes of Transbuccal Approach Versus Transoral Fixation in Open Reduction and Internal Fixation of Mandibular Angle Fracture: Transbuccal Approach Versus Transoral Fixation in ORIF of Mandibular Angle Fracture - Khalil, Muhammad; Akhtar, Uzair Bin; Akram, Komal; Khawaja, Mustafa Ayub; Jabbar, Maria; Asif, Almira (Pakistan Journal of Health Sciences, 2026)
Fractures of the mandibular angle pose surgical challenges due to limited access and complex anatomy. The transbuccal approach improves access but requires a small skin incision, while the transoral approach avoids external scars but may limit visualization. Objectives: To compare transbuccal and transoral approaches for open reduction and internal fixation (ORIF) of mandibular angle fractures with respect to surgical time, intraoperative access, and postoperative occlusion. Methods: Eighty patients with isolated unilateral mandibular angle fractures were prospectively assigned to transoral (n=40) or transbuccal (n=40) fixation. Surgical time, intraoperative accessibility (scored 1–3), and postoperative occlusion were recorded. Data normality was assessed using the Shapiro-Wilk test, and comparisons were made using the Mann–Whitney U test (p<0.05). Results: The transoral approach significantly reduced median surgical time compared to transbuccal fixation (41 (15) vs. 69 (4) minutes; U=4.000, p<0.001). Conversely, intraoperative accessibility was superior with the transbuccal approach (1 [1] vs. 2 (0); U=314.000, p<0.001). Postoperative occlusion was comparable between groups (0 (0) vs. 0 (0); U=783.000, p=0.765). Conclusions: Both approaches provide similar postoperative occlusal outcomes. The transbuccal method offers enhanced intraoperative access, whereas the transoral technique reduces operative time and avoids external scars. Surgical technique should be selected based on case complexity, access requirements, and cosmetic considerations.